In vitro biological activities of Calamintha nepeta L. aqueous extracts - Salhi, Nadia; Deluyker, Dorien; Bito, Virginie; Zaid, Abdelhamid; El Rhaffari, Lhoussaine (Journal of applied biomedicine, 2024)
AIM: This study aimed to investigate the phenolic composition, antioxidant capacity, and toxicity of aqueous extracts of Calamintha nepeta L. leaves and their potential vasorelaxant effects. METHODS: Aqueous extracts of Calamintha nepeta L. were prepared by three extraction methods: decoction, infusion, and maceration. The total phenolic contents of the extracts and their antioxidant properties were investigated. The toxicity was evaluated by Artemia salina lethality bioassay. The decoction extract was analyzed by HPLC for its chemical profile and was also used to evaluate the vasorelaxant effect on thoracic aortic rings isolated from healthy Sprague Dawley rats. Pre-contraction was induced by phenylephrine, followed by cumulative doses of the extract (0.001 up to 250 μg/ml). RESULTS: Aqueous extracts of Calamintha nepeta L. showed noticeable radical scavenging and chelating activities. However, the decoction extract exhibited the most powerful antioxidant capacity. No toxicity was recorded for the extracts obtained by decoction and infusion. Caffeic acid, quercetin, and rosmarinic acid were the main identified compounds. Notably, the aqueous extract obtained by decoction induced significant relaxation in endothelium-intact aortic rings at lower concentrations, and at higher concentrations in denuded aortic rings. CONCLUSION: This study reveals that Calamintha nepeta L. extracted with a decoction method possesses potent antioxidant capacity and has an endothelium-dependent vasorelaxant effect.
Keywords: listy rostlin; antioxidancia; Male; potkani Sprague-Dawley; rostlinné extrakty; vazodilatancia; Artemia; mužské pohlaví; fenoly; Aorta, Thoracic; Vasodilator Agents; krysa rodu Rattus; aorta thoracica; Animals; Plant Extracts; Antioxidants; zvířata; Plant Leaves; Rats; Phenols; Rats, Sprague-Dawley